Impact of Stacking Sequence and Sulfurization Duration on the Growth of Pyrargyrite Ag3sbs3 Absorber Layers - Radhalayam, D (Academic Press, 2024)
Pyrargyrite Ag3SbS3 is a promising absorber for thin-film solar cells. In this study, the impact of precursor stacking sequence and sulfurization duration on the growth and properties of Ag3SbS3 films was investigated. Initially, the Ag3SbS3 films produced by depositing Sb/Ag and Ag/Sb/Ag metal stacks and then sulfurizing at 300 °C crystallized in rhombohedral structure with (113) preferred orientation. The film produced from the Sb/Ag stack had a uniform and large-grained morphology up to a thickness of 1150 nm, and a direct bandgap of 1.65 eV; whereas the film prepared with the Ag/Sb/Ag stack exhibited nonuniform grain morphology with decreased film thickness, and increased bandgap energy (1.70 eV). Secondly, the Ag3SbS3 films produced from the Sb/Ag stack by increasing sulfurization duration from 10 to 90 min increases the crystallite size from 26 to 27 nm, enhances the grain compactness and uniformity, varies the bandgap in the range of 1.65–1.69 eV, and electrical resistivity. The solar cells fabricated using the films produced by sulfurizing the Sb/Ag stack for 30 min duration exhibited a maximum power conversion efficiency of 0.52% with an VOC of 471.6 mV, JSC of 2.0 mA/cm2, and FF of 55.0%. This study offers a pathway for the advancement of Ag3SbS3 thin-film solar cells. © 2024